2009
DOI: 10.1083/jcb.200908075
|View full text |Cite
|
Sign up to set email alerts
|

Opposite-polarity motors activate one another to trigger cargo transport in live cells

Abstract: Mechanical interactions between any two opposite-polarity motors are necessary and sufficient for bidirectional organelle transport in live cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
195
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(220 citation statements)
references
References 68 publications
21
195
3
Order By: Relevance
“…A similar mechanism has been proposed for regulating kinesin/dynein transport on microtubules via the presence of tau-protein binding to the microtubule (42). Modifiers that alter the number of engaged motors in effect would eliminate or bias (43)(44)(45) the inherent tug of war that would exist between opposing motors as observed in this study. Future efforts to define the various regulatory mechanisms that govern intracellular transport will benefit from parallel in vitro single molecule biophysical and in vivo cell biological approaches.…”
Section: In-phasementioning
confidence: 55%
“…A similar mechanism has been proposed for regulating kinesin/dynein transport on microtubules via the presence of tau-protein binding to the microtubule (42). Modifiers that alter the number of engaged motors in effect would eliminate or bias (43)(44)(45) the inherent tug of war that would exist between opposing motors as observed in this study. Future efforts to define the various regulatory mechanisms that govern intracellular transport will benefit from parallel in vitro single molecule biophysical and in vivo cell biological approaches.…”
Section: In-phasementioning
confidence: 55%
“…T he active intracellular transport of a large variety of cargos is fundamental for many cellular processes. In such transport, molecular motors bound to the cargo usually work together in teams (1)(2)(3). These teams can consist of one or several types of motor, with varying mechanical properties, including velocity, directionality, and processivity (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Quantitative analyses of motor numbers in living cells have shown that a few motors of each type bind to the same organelle, where they coordinate and control each other's activity (3,6,7). The number of bound motors is remarkably similar in different systems, usually ranging from one to five motors of each type (7)(8)(9)(10), although in a few cases larger numbers were also reported (11,12).…”
mentioning
confidence: 96%
“…It is usually bidirectional, which is thought to help motors to bring their cargo to the right destination (3). Intracellular transport is mediated by motor proteins belonging to the kinesins and dyneins that bind to the organelles and hydrolyze ATP to move their cargo along the microtubules (MTs) (4).…”
mentioning
confidence: 99%